Impact of Soft Skills Training on Behaviour of Employees - Intel Corporation - Wong Pooi Hang, Annie; Singh Sikarwar, Tarika; Nordin, Nor Alia Balqis; Rosley, Norakma Irwany; Mudzaffar, Noureysha; Shokri, Nur Adriana Sofea; Patel, Neha; Daisy Mui Hung, Kee (Asia Pacific Journal of Management and Education (APJME), 2024)
Intel Corporation is a global leader in designing and producing essential goods and technologies that drive the cloud. This study aims to examine how soft skills training affects behaviour of Intel Corporation's employees. The research strives to identify the subtle ways soft skills development brings to Intel's success through rigorous data collection. A survey questionnaire was designed to gather quantitative data regarding the employees' experiences with soft skills training at Intel Corporation Malaysia. The survey questionnaire has taken into account the wording of the questions, the order of the questions, and the administration of the survey to ensure that the results obtained are accurate and consistent. A sample of 150 employees of Intel Corporation in Malaysia responded to the study, providing diverse perspectives on how soft skills training can impact employees’ behavior. Appropriate statistical tools were used to assess how soft skills training affected the employees’ behavior. The findings have significant implications for Intel Corporation.Keywords: Data collection, Employee behavior, Intel Corporation, Malaysia, Soft skills training, Survey questionnaire.